2022
DOI: 10.1007/s11096-022-01437-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of early versus late caffeine therapy in managing apnoea of prematurity among preterm infants: a retrospective cohort study

Abstract: Background Early administration of intravenous (IV) caffeine (initiation within 2 days of life) is an effective treatment strategy for the management of apnoea of prematurity among infants. However, the safety and effectiveness of early administration of oral caffeine treatment is not be fully established. Aim We aimed to compare the effectiveness and safety of early versus late caffeine therapy on preterm infants’ clinical outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…Lodha et al 8 investigated <29 weeks’ GA infants who received caffeine within 2 days and found that the odds of neurological injury at discharge and significant neurodevelopmental impairment at 2 years were reduced compared with those in the late caffeine group, although the odds of any neurodevelopmental impairment were similar. Association between lower rates of BPD and preterm brain injury and early caffeine use has been reported in other studies 17–21…”
Section: Discussionsupporting
confidence: 56%
“…Lodha et al 8 investigated <29 weeks’ GA infants who received caffeine within 2 days and found that the odds of neurological injury at discharge and significant neurodevelopmental impairment at 2 years were reduced compared with those in the late caffeine group, although the odds of any neurodevelopmental impairment were similar. Association between lower rates of BPD and preterm brain injury and early caffeine use has been reported in other studies 17–21…”
Section: Discussionsupporting
confidence: 56%
“…In the Caffeine for Apnea of Prematurity Trial (CAP trial) [1], there was no significant difference in mortality between the caffeine group and the non-caffeine group. Otherwise, in studies conducted by Dobson et al [16], Patel et al [18], Shenk et al [23], Szatkowski et al [21], and Yun et al [14] as well as in this current meta-analysis, there was a significantly higher rate of mortality in the early caffeine group. Given the improvement in other outcomes, these results may potentially be due to survival bias favoring the late caffeine initiation group.…”
Section: Discussioncontrasting
confidence: 39%
“…After removing duplicate records and studies that did not meet the eligibility criteria, 21 studies remained. Following the application of our inclusion and exclusion criteria, a total of 11 studies were included in the final review [3,[14][15][16][17][18][19][20][21][22][23]. Among the patients included in these 11 studies, 78,332 received early caffeine administration, while 44,237 received late caffeine administration.…”
Section: Resultsmentioning
confidence: 99%
“…Its use for neuroprotection in neonates and prevention of hypoxemic episodes has been investigated and proven effective (Bucher & Duc, 1988; Carty et al, 2011; Oliphant et al, 2023; Rhein et al, 2014). Caff is generally administered during early postnatal life, however, it is also used in some infants with persisting apnea in later life (Hand et al, 2016; Lodha et al, 2019; Nylander Vujovic et al, 2020; Yun et al, 2022). Some studies showed better respiratory (Yun et al, 2022) and neurological outcomes (Lodha et al, 2019) with early treatment, but there was a higher risk of mortality (Yun et al, 2022), while others showed that late treatment was better for reducing IH (Oliphant et al, 2023), or no significant difference (Hand et al, 2016; Nylander Vujovic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Caff is generally administered during early postnatal life, however, it is also used in some infants with persisting apnea in later life (Hand et al, 2016; Lodha et al, 2019; Nylander Vujovic et al, 2020; Yun et al, 2022). Some studies showed better respiratory (Yun et al, 2022) and neurological outcomes (Lodha et al, 2019) with early treatment, but there was a higher risk of mortality (Yun et al, 2022), while others showed that late treatment was better for reducing IH (Oliphant et al, 2023), or no significant difference (Hand et al, 2016; Nylander Vujovic et al, 2020). These discrepancies prompted us to examine the effects of later Caff treatment, after the IH insult.…”
Section: Introductionmentioning
confidence: 99%